Efficacy and safety of treatment regimens for patients with metastatic, locally advanced, or recurrent breast cancer carrying BRCA1/BRCA2 pathogenic variants: A network meta-analysis - Zhu, Yingxuan; Li, Yang; Liu, Weida; Zhou, Ruozhu; Tse, Lap Ah; Wang, Yang; Li, Wei (Frontiers in Oncology, 2023)
Objective This study aimed to conduct a network meta-analysis to synthesize the efficacy and safety of various pharmacotherapies for metastatic or locally advanced breast cancer patients with BRCA1/2 mutations. Methods The search was conducted in Embase, PubMed, and Cochrane Library (CENTRAL), from inception to 11 May 2022. Additional studies were looked for by searching the references of the included papers. This network meta-analysis included searches for randomized controlled trials of pharmacotherapy treated metastatic, locally advanced, or recurrent breast cancer patients with BRCA mutations. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines were followed in conducting and reporting this systematic review. We used the GRADE method to evaluate evidence's certainty (Grading of Recommendations Assessment, Development, and Evaluation). Frequentist random-effect model was applied. Objective response rate (ORR), progression-free survival (PFS) rates at the 3rd, 12th, and 24th months, as well as overall survival (OS) rates at the 3rd, 12th, 24th, and 36th months; rates of any-grade adverse events. Results Nine randomized controlled trials, including 1912 patients with BRCA mutations were obtained involving six treatment regimens. The PARP inhibitors orchestrated with platinum-based chemotherapy was found to be the most effective with a pooled odds ratio (OR) of 3.52 (95% CI 2.14, 5.78) regarding ORR; 1.53 (1.34,1.76), 3.05 (1.79, 5.19), and 5.80 (1.42, 23.77) for 3-month, 12-month and 24-month PFS; and 1.04 (1.00, 1.07), 1.76 (1.25, 2.49) and 2.31 (1.41, 3.77) for a 3-month, 12-month and 36-month OS, compared with non-platinum-based chemotherapy. However, it can also pose an elevated risk of some adverse events. Platinum-based chemotherapy alone or PARP inhibitors were also found to significantly improve ORR, PFS, and OS compared with non-platinum-based chemotherapy, and platinum-based chemotherapy took advantage over PARP inhibitors. Evidence about programmed death-ligand 1(PD-L1) inhibitor and sacituzumab govitecan (SG) had low quality and insignificant results. Conclusions Among all treatment regimens, PARP inhibitor orchestrated with platinum exhibited the best efficacy, although a trade-off of elevated risk of some types of adverse events is inevitable. Future research on direct comparisons between different treatment regimens targeting specifically the breast cancer patients with BRCA1/2 mutations with pre-specified adequate sample size is warranted.